Thyrotropin Binding Inhibiting Antibody (TBIAb) in Graves’ Disease - Cho, Won Yong (Korean J Intern Med, 1988)
To determine the nature of TBIAb in Graves’ disease, TBIAb was measured and correlated to various clinical, thyroid functional indices and thyroid autoantibodies. The incidence of TBIAb in untreated Graves’ patients, patients in treatment and those in remission was 70.9%, 53.1% and 19.2%, respectively. With respect to clinical indices, there was no correlation between TBIAb and the presence of exophthalmos or periodic paralysis, onset age, diseage duration or sex, but goiter size on initial examination did show significant correlation (r=0.95). Regarding the indices of thyroid function, 20min 99m-Tc uptake (r=0.28), free T4 index (r=0.39) and free T3 index (r=0.40) were well correlated to TBIAb activity. Also Grave’s patients with strong antimicrosomal activity exhibited a high incidence of TBIAb positiveness.